Gastroesophageal resuscitative occlusion of the aorta prolongs survival in a lethal liver laceration model. Issue 5 (27th October 2021) - McCracken, Brendan M.; Tiba, Mohamad Hakam; Colmenero Mahmood, Carmen I.; Leander, Danielle C.; Greer, Nicholas L.; Plott, Jeffery S.; Shih, Albert J.; Wang, Stewart C.; Eliason, Jonathan L.; Ward, Kevin R.
Abstract : This work describes the utility of an investigational device known as GROA for temporary aortic occlusion which stanches non-compressible abdominal hemorrhage and improved survival in a swine model of rapidly lethal liver laceration. Abstract : BACKGROUND: Noncompressible torso hemorrhage management remains a challenge especially in the prehospital setting. We evaluated a device designed to occlude the aorta from the stomach (gastroesophageal resuscitative occlusion of the aorta [GROA]) for its ability to stop hemorrhage and improve survival in a swine model of lethal liver laceration and compared its performance to resuscitative endovascular balloon occlusion of the aorta (REBOA) and controls. METHODS: Swine (n = 24) were surgically instrumented and a 30% controlled arterial hemorrhage over 20 minutes was followed by liver laceration. Animals received either GROA, REBOA, or control (no treatment) for 60 minutes. Following intervention, devices were deactivated, and animals received whole blood and crystalloid resuscitation. Animals were monitored for an additional 4 hours. RESULTS: The liver laceration resulted in the onset of class IV shock. Mean arterial blood pressure (MAP) (standard deviation) decreased from 84.5 mm Hg (11.69 mm Hg) to 27.1 mm Hg (5.65 mm Hg) at the start of the intervention. Seven of eight control animals died from injury prior to the end of the intervention period with a median survival (interquartile) time of 10.5 minutes (12 minutes). All GROA and REBOA animals survived the duration of the intervention period (60 minutes) with median survival times of 86 minutes (232 minutes) and 79 minutes (199 minutes) after resuscitation, respectively. The GROA and REBOA animals experienced a significant improvement in survival compared with controls ( p = 0.01). Resuscitative endovascular balloon occlusion of the aorta resulted in higher MAP at the end of intervention 114.6 mm Hg (22.9 mm Hg) compared with GROA 88.2 mm Hg (18.72 mm Hg) ( p = 0.024), as well as increased lactate compared with GROA 13.2 meq·L −1 (1.56 meq·L −1 ) versus 10.5 meq·L −1 (1.89 meq·L −1 ) ( p = 0.028). Histological examination of the gastric mucosa in surviving animals revealed mild ischemic injury from both GROA and REBOA. CONCLUSION: The GROA and REBOA devices were both effective at temporarily stanching lethal noncompressible torso hemorrhage of the abdomen and prolonging survival. Abstract :